Chiral hybrid manganese(ii) halide clusters with circularly polarized luminescence for X-ray imaging. Issue 9 (9th February 2023) - Wang, Mengzhu; Wang, Xiaoming; Zhang, Bintao; Li, Feiyang; Meng, Haixing; Liu, Shujuan; Zhao, Qiang
Abstract : Two pairs of enantiomorphic organic–inorganic hybrid manganese(ii ) halide clusters show excellent CPL properties and work as scintillators in X-ray detection and imaging. Abstract : Chiral organic–inorganic hybrid metal halides with high photoluminescence quantum yield (PLQY) and high luminescence dissymmetry factor ( g lum ) offer a new platform for multifunctional photoelectric applications. Herein, we report two pairs of chiral organic–inorganic hybrid manganese(ii ) halide clusters ( R / S -3-aminopyrrolidine dihydrochloride)6 (Mn3 Cl12 )(Cl)6 ( R / S -1 ) and ( R / S -1, 2-diaminopropane dihydrochloride)3 (Mn3 Cl12 ) ( R / S -2 ). Both of them have high PLQY (more than 42%) under ambient conditions; in particular, the PLQY of R / S -2 reached 85%. More importantly, the g lum value of R / S -1 (| g lum | = 0.0071) is 3.5 times that of R / S -2 (| g lum | = 0.002), showing excellent circularly polarized luminescence (CPL) properties. Through the structural analysis of single crystals, we reveal that the directional arrangement of chiral ligands in manganese cluster molecules has the ability to amplify the CPL properties. Furthermore, based on the excellent luminescence properties of R / S -2, we show examples of their applications as scintillators in X-ray detection and imaging. To our knowledge, this is the first report of chiral manganese(ii ) halide scintillators. This research provides rational guiding principles for the design and preparation of multifunctional chiral organic–inorganic hybrid metal halides.